A dimethoxypillar[5]arene/azastilbene host–guest recognition motif and its applications in the fabrication of polypseudorotaxanes. Issue 24 (4th June 2019) - Wang, Liyun; Xia, Danyu; Chao, Jianbin; Zhang, Junjie; Wei, Xuehong; Wang, Pi
Abstract : A host–guest recognition motif based on 1, 4-dimethoxylpillar[5]arene (DMP5 ) and guest trans -4, 4′-vinylenedipyridine ( trans -G1 ) was fabricated and applied to construct metallosupramolecular polypseudorotaxanes. Abstract : Pillar[ n ]arenes, known as the fifth generation of host macrocycles since 2008, have become a popular topic over the past ten years. Until now, the studies of pillar[ n ]arenes were mainly focused on pillar[5]arenes owing to their easy synthesis and high yields. In particular, 1, 4-dimethoxypillar[5]arene (DMP5 ), which shows a simple structure, efficient synthesis and high yield, has played important roles in the construction of various advanced supramolecular architectures. However, DMP5 has only displayed host–guest binding properties towards some guests. Therefore, the investigation of the host–guest chemistry ofDMP5 should be able to greatly promote the development of pillararene chemistry. Herein, a photosensitive azastilbene derivative was chosen as a neutral guest to study the host–guest binding and stimuli-responsive behavior withDMP5 . In addition, the binding behavior ofDMP5 towards a series of analogous neutral guest molecules was investigated to study the driving forces of the host–guest interaction betweenDMP5 and the azastilbene guest. Moreover, the [2]pseudorotaxane based onDMP5 and the azastilbene guest was used to construct a polypseudorotaxane via metal coordination.